Examining the effects of socioeconomic development on fine particulate matter (PM2.5) in China's cities using spatial regression and the geographical detector technique - Zhou, Chunshan; Chen, Jing; Wang, Shaojian (The Science of the total environment, 2018)
•The direction and strength of the link between PM2.5 level and their drivers are analyzed.•Spatial regression and geographical detector techniques are used.•A spatial agglomeration effect was identified in city-level PM2.5 level.•Population density, industrial structure, industrial dust, and road density increase PM2.5 level.•Trade openness and electricity consumption have no significant effect on PM2.5 level. [Display omitted] The frequent occurrence of extreme smog episodes in recent years has begun to present a serious threat to human health. In addition to pollutant emissions and meteorological conditions, fine particulate matter (PM2.5) is also influenced by socioeconomic development. Thus, identifying the potential effects of socioeconomic development on PM2.5 variations can provide insights into particulate pollution control. This study applied spatial regression and the geographical detector technique for assessing the directions and strength of association between socioeconomic factors and PM2.5 concentrations, using data collected from 945 monitoring stations in 190 Chinese cities in 2014. The results indicated that the annual average PM2.5 concentrations is 61±20μg/m3, and cites with more than 75μg/m3 were mainly located in North China, especially in Tianjin and Hebei province. We also identified a marked seasonal variation in concentrations levels, with the highest level in winter due to coal consumption, lower temperatures, and less rainfall than in summer. Monthly variations followed a “U-shaped” pattern, with a down trend from January and an inflection point in September and then an increasing trend from October. The results of spatial regression indicated that population density, industrial structure, industrial soot (dust) emissions, and road density have a significantly positive effect on PM2.5 concentrations, with a significantly negative influence exerted only by economic growth. In addition, trade openness and electricity consumption were found to have no significant impact on PM2.5 concentrations. Using the geographical detector technique, the strength of association between the five significant drivers and PM2.5 concentrations was further analyzed. We found notable differences among the variables, with industrial soot (dust) emissions playing a greater role in the PM2.5 concentrations than the other variables. These results will be helpful in understanding the dynamics and the underlying mechanisms at work in PM2.5 concentrations in China at the city level, and thereby assisting the Chinese government in employing effective strategies to tackle pollution.